Proceedings of the 4th Clinical Natural Language Processing Workshop 2022
DOI: 10.18653/v1/2022.clinicalnlp-1.2
|View full text |Cite
|
Sign up to set email alerts
|

PLM-ICD: Automatic ICD Coding with Pretrained Language Models

Abstract: Automatically classifying electronic health records (EHRs) into diagnostic codes has been challenging to the NLP community. State-ofthe-art methods treated this problem as a multilabel classification problem and proposed various architectures to model this problem. However, these systems did not leverage the superb performance of pretrained language models, which achieved superb performance on natural language understanding tasks. Prior work has shown that pretrained language models underperformed on this task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Huang, et al (2022) [12] proposed a PLM to predict ICD codes (PLM-ICD) that tackles the challenges of previous pretrained models, namely the use of domain-specific pretraining, segment pooling for the long input sequence problem, and level attention for the large label set problem. Experiments were conducted over MIMIC-II and MIMIC-III datasets.…”
Section: Pretrained Language Modelsmentioning
confidence: 99%
“…Huang, et al (2022) [12] proposed a PLM to predict ICD codes (PLM-ICD) that tackles the challenges of previous pretrained models, namely the use of domain-specific pretraining, segment pooling for the long input sequence problem, and level attention for the large label set problem. Experiments were conducted over MIMIC-II and MIMIC-III datasets.…”
Section: Pretrained Language Modelsmentioning
confidence: 99%
“…RPGNet is trained using Reinforcement Learning (RL) in an adversarial fashion. [17] PLM-ICD use Pretrained Language Models to extract the contextualuzed representations, it spotted three main issues through the experiments: 1) large label space, 2) long input sequences, and 3) domain mismatch between pretraining and fine-tuning. It's the sota method for ICD classification.…”
Section: Baselinesmentioning
confidence: 99%
“…We report a variety of metrics that are commonly used by previous studies on this task [16,9,17], including micro-averaged and macro-averaged metrics. Micro-averaged metrics are calculated by treating each sample as a separate prediction, while macro-averaged metrics are calculated by averaging metrics computed per label.…”
Section: Metricmentioning
confidence: 99%
“…LLMs possess the ability to label and classify free form text, an attribute that can be integrated into the coding process itself. For instance, studies have demonstrated the feasibility of employing LLMs to automatically classify electronic health records into International Classification of Diseases codes [ 17 ]. Furthermore, LLMs have been successfully employed to classify free text in regulatory documents into specific predefined sections [ 18 ], and to code text data that require deductive analysis [ 19 ], addressing a long-standing challenge in clinical research.…”
Section: Applications On Free Text Narrativesmentioning
confidence: 99%